THE INFLUENCE OF WORK CAPABILITY AND INFRASTRUCTURE FACILITIES ON WORK READINESS IN COMMUNICATION AND ELECTRONICS OPERATIONS ISWAHJUDI AIR FORCE BASE - Hakim , Arief Rahman; Kiswara, Geger Jaka; Marlina, Rina (Universitas Islam Lamongan, 2023)
This research was conducted to analyze the influence of personnel capabilities, facilities and infrastructure partially and simultaneously on the readiness of Iswahjudi Air Force communication and electronics operations. In order to achieve these objectives, this study used a quantitative method with a cross-sectional survey research design using a questionnaire with a Likert scale. The sampling technique used proportionate stratified random sampling, obtained 88 samples. Data analysis technique by doing descriptive statistics and inferential statistics, using simple regression and multiple regression, with a significance of 5% (0.05). The results of the study found that the ability of personnel had a significant, positive effect on the readiness of Iswahjudi Lanud's communications and electronics operations. The facilities and infrastructure have a significant, positive effect on the readiness of communications and electronics operations at Iswahjudi Air Force Base, and together the capabilities of personnel, facilities and infrastructure have a significant and positive effect on the readiness of communications and electronics operations at Iswahjudi Air Force Base